Análisis de los elementos de la justicia transicional en el contexto de la democracia constitucional (2021)
This article studies both the model of State called constitutional democracy, adopted in most countries of the Latin American region, and the jurisprudential development of the Inter-American Court, which is related to the pillars of transitional justice: justice, truth, reparation and non-repetition. To this end, an analytical perspective is used to present, in a structured manner, those guidelines that specify the scope of the obligations of respect and guarantee that correspond to the States that are undergoing a process of democratic transition in the Latin American region. The conclusions reached in this research show the need to create and promote dialogue between the courts and the States parties, not as a result of an obligation but as a trend towards direct and immediate justiciability of human rights for the consolidation of a comprehensive model of a democratic and constitutional State.